TRENDS IN CUSTOMER EXPERIENCE MARKETING FOR ENTREPRENEURS IN THE EASTERN REGION OF PARAGUAY - Cañete Britez, Walter (Revista Gênero e Interdisciplinaridade, 2023)
The research focused on analyzing the Customer Experience Marketing (MEC) strategies implemented by entrepreneurs in Ciudad del Este and Presidente Franco. Common patterns, specific challenges and the influence of sectoral characteristics on these strategies were identified. The target population was clients who interacted with these strategies, and stratified random sampling was used to obtain a representative sample. The survey, made up of 10 closed questions, revealed significant insights. The frequency of visits to local businesses was primarily weekly or occasional, and most never participated in loyalty programs. Communication about offers and promotions showed areas for improvement, and overall customer satisfaction was variable. The importance of customer service and the quality of products or services was highlighted as influential factors in the choice of local businesses. The majority did not share their experiences online and preferred to receive information about offers through social networks. Suggested proposals include staff training, improved communication and personalization, sector collaboration and focus on digital experience to enhance Customer Experience Marketing in the region.